Observational study to characterize socio-demographic data and clinical presentation in patients with acute exacerbation of chronic obstructive pulmonary disease - Sharma, Amit; Bhardwaj, Mamta; Jain, Prerna; Tayal, Devika (International Journal of Research in Medical Sciences, 2022)
Chronic obstructive pulmonary disease (COPD) is a common inflammatory disease with high global morbidity and mortality. It is characterized by poorly reversible airway obstruction. The major risk factor associated is smoke exposure which leads to chronic respiratory failure. Various chronic medical conditions commonly coexisting with COPD include coronary artery disease, diabetes mellitus, osteoporosis and muscle weakness. Co-morbid conditions should be managed appropriately along with treatment of COPD. Present observational study was undertaken to characterize socio-demographic data, clinical presentation and possible co-morbidities (cardiac, diabetes mellitus, and hypertension) in COPD patients. The observed data was analyzed to study prevalence of all parameters gender wise and relation with diagnostic technique i.e. chest X-ray and electrocardiography (ECG) for cardiac screening. Therefore, in the following study, elderly and male patients were prominently affected by COPD with common symptoms of cough, breathlessness, expectoration, fever and chest pain. Diabetes is one of the co-morbidities observed in this set of patients. Hence, random blood sugar (RBS) and glycated hemoglobin (HbA1c) parameters were deranged in this cohort of patients. Additionally, ECG was also observed to be abnormal in few patients. Conclusively, this study highlighted various demographic features, clinical symptoms and comorbidities responsible for health burden of COPD patients.